2017
DOI: 10.1002/jbm.b.33941
|View full text |Cite
|
Sign up to set email alerts
|

Improved hemodialysis with hemocompatible polyethersulfone hollow fiber membranes: In vitro performance

Abstract: We show that addition of nanozeolite (NZ) and vitamin E D-α-Tocopherol polyethylene glycol succinate (TPGS or T) considerably improves the performance of polyethersulfone (PES or P) hollow fiber membrane (HFM) for hemodialysis. Nanocomposite HFMs were manufactured using PES as a polymer, TPGS as an additive and NZ as a filler to give a composite membrane called PT-NZ. HFMs were spun by dry-wet spinning principle based on liquid-liquid phase separation. TPGS and NZ were successfully incorporated in HFMs, as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Haemolysis refers to the lysis of RBCs when the human blood comes in contact with a membrane material. Therefore, it is desirable to have haemolysis value within the permissible haemolytic limit, which is 5% as prescribed by the ASTM F‐756‐08 standard (Modi et al, 2018c; Verma, Modi, Singh, Teotia, & Bellare, 2018). In this study, the developed materials showed the haemolysis value <5%, that is, within the prescribed limit, which indicated that these HFMs are suitable for blood‐contacting applications (Figure 9a) (Padalhin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Haemolysis refers to the lysis of RBCs when the human blood comes in contact with a membrane material. Therefore, it is desirable to have haemolysis value within the permissible haemolytic limit, which is 5% as prescribed by the ASTM F‐756‐08 standard (Modi et al, 2018c; Verma, Modi, Singh, Teotia, & Bellare, 2018). In this study, the developed materials showed the haemolysis value <5%, that is, within the prescribed limit, which indicated that these HFMs are suitable for blood‐contacting applications (Figure 9a) (Padalhin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting membrane showed good biocompatibility, but poor UF coefficient (Dahe et al, 2011). Verma at al. (2017) used vitamin E (D-α-Tocopherol polyethylene glycol succinate) (TPGS) and nanozeolite (NZ) to improve the biocompatibility of PES HF membranes.…”
Section: Optimization Of Pesmentioning
confidence: 99%
“…In addition, the adsorption of naturally existing hydrophobic proteins such as albumin on the membrane surface also causes protein loss. Alternatively, enhancement of membrane permeability and surface hydrophilicity is a viable strategy to improve convective separation of middle molecule uremic toxins and minimize the interaction between membrane surface and hydrophobic proteins …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, enhancement of membrane permeability and surface hydrophilicity is a viable strategy to improve convective separation of middle molecule uremic toxins and minimize the interaction between membrane surface and hydrophobic proteins. 11,12 Therefore, modifications are needed to achieve excellent membrane separation performance with minimal adverse effects. Incorporation of inorganic nanomaterials in membrane matrices has become an emerging trend to enhance the membrane permeability, selectivity, and physicochemical properties against chemical degradation and thermal instability.…”
Section: Introductionmentioning
confidence: 99%